Fouling resistant superhydrophilic membrane - Gong, Zhuang Ming (Nanyang Technological University, 2022)
Fouling in membrane systems is one of the most commonly encountered issues in wastewater treatment processes. Simply put, this results in a decreased amount of treated effluent or increase in operating costs associated with the higher energy demand required to pump the feed at a higher pressure. Given that fouling is such a major problem in wastewater treatment, there have been numerous measures developed to control and mitigate it. One such strategy involves the use of chemicals as both a preventive and corrective measure against fouling. While chemicals remain as a popular fouling control measure, there are still certain drawbacks and limitations that have yet to be addressed. For example, the regular usage of chemicals contributes significantly to the operating costs of the treatment plant due to the inherent costs of the chemicals themselves. Additionally, unwanted byproducts such as toxic chemical sludge is generated, and extra costs associated with the handling and disposal of such waste also contributes to the overall operating costs. Hence, there is a motivation for current wastewater treatment plants to reduce their dependency on chemicals and focus on more sustainable methods for fouling control.